1992
DOI: 10.1021/bi00166a017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human calmodulin-like protein expressed in Escherichia coli

Abstract: The protein-coding region of an intronless human calmodulin-like gene [Koller, M., & Strehler, E. E. (1988) FEBS Lett. 239, 121-128] has been inserted into a pKK233-2 expression vector, and the 148-residue, M(r) = 16,800 human protein was purified to apparent homogeneity by phenyl-Sepharose affinity chromatography from cultures of Escherichia coli JM105 transformed with the recombinant vector. Several milligrams of the purified protein were obtained from 1 L of bacterial culture. A number of properties of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 54 publications
4
65
0
Order By: Relevance
“…Bradford protein assay kits were from Bio-Rad. Recombinant human CaM was purified from Escherichia coli by published procedures (28). DNA purification kits and Ni 2ϩ -NTA agarose were purchased from QIAGEN (Chatsworth, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Bradford protein assay kits were from Bio-Rad. Recombinant human CaM was purified from Escherichia coli by published procedures (28). DNA purification kits and Ni 2ϩ -NTA agarose were purchased from QIAGEN (Chatsworth, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Like calmodulin (CaM), CLP contains four "EF-hand" Ca 2ϩ binding motifs but has an overall Ca 2ϩ binding affinity that is ϳ10-fold lower than in CaM (4). The x-ray crystal structure indicates that Ca 2ϩ -CLP is very similar in overall shape to Ca 2ϩ -CaM, although a notable difference is observed in the angle of the central helix with respect to the N-and C-terminal lobes.…”
mentioning
confidence: 99%
“…Accordingly, although CLP can substitute for CaM in binding and activation of some targets (e.g. CaM kinase II), many CaM targets either bind CLP with reduced affinity or not at all (4,6). On the other hand, recent data have shown that CLP interacts with unique targets, specifically with the unconventional myosin Myo-10 (7).…”
mentioning
confidence: 99%
“…2+ -Dependent Electrophoretic Shift Assay The SDS-PAGE electrophoretic mobility assay was carried out according to published protocols (11,12) . Briefly, samples of pure WT CaM, ADA-labeled engineered CaM proteins, and lysozyme were prepared at equal concentrations, and 10 µg of each protein was loaded on 4-12% gradient gels.…”
Section: Camentioning
confidence: 99%